2019
DOI: 10.1007/978-3-030-21752-5_2
|View full text |Cite
|
Sign up to set email alerts
|

Towards Transparency in Email Tracking

Abstract: Tracking technologies have become ubiquitous, not only on websites but also in email messages. However, while protection and transparency tools exist for the web, no such tools exist for email messages, thus obscuring privacy violations. We introduce the PrivacyMail platform to assist with the automated analysis of email messages. The platform automatically analyzes commercial mailing lists, making it easier to detect different forms of tracking. Our platform introduces transparency about the practices of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…In fact it has been suggested that almost 16% of personal conversation emails and 99% of bulk email communications in users' inboxes contain some form of tracking mechanisms [26]. These findings are also confirmed by several academic studies regarding newsletter emails [22,4,3].…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In fact it has been suggested that almost 16% of personal conversation emails and 99% of bulk email communications in users' inboxes contain some form of tracking mechanisms [26]. These findings are also confirmed by several academic studies regarding newsletter emails [22,4,3].…”
Section: Introductionmentioning
confidence: 64%
“…Next, the request-URL represents the address of the remote resource. In newsletter emails, senders often embed personalized tracking tokens in the request-URL [9,22,15,17]. Such a tracking token could be any string that maps to the recipient email address, or identity, at the server side.…”
Section: Http Requestsmentioning
confidence: 99%
“…They considered these tokens as Personally Identifying Information (PII) and looked for cases where they are shared with third parties. Haupt et al [21] and Maass et al [30] use multiple subscription to find personalized URLs, by comparing the URL structure of emails sent to multiple users.…”
Section: Remote Resources and Http Requestsmentioning
confidence: 99%
“…Previous studies consider the distribution of third-parties in emails as indication of email tracking [4,11,30,23]. In these studies, the URL of third-party contents use a different domain name than the email sender, or the website on which the email address was registered.…”
Section: Distinction Between Third Party and First Party Is Blurry In Emailmentioning
confidence: 99%
See 1 more Smart Citation